(untitled) (Revista Apotheke, 2021)
Proposing experiences beyond the spaces of educational institutions can bring unique and very significant experiences for students and teachers, whether in Higher Education or Basic Education. The experience we refer to here, as highlighted by John Dewey (2010, 1979a, 1979b, 1978), deals with ways of experiencing moments and situations that are, at the same time, singular and plural, collective constructions of very webs of ideas and thoughts, in addition to the disciplinary and content experiences present in schools and higher education institutions. Based on these premises, this article approaches different moments of aesthetic experiences in the educational context, carried out in public spaces in São Paulo, with undergraduate students in Pedagogy and Physical Education and also from a graduate program, and in the Pantanal of Mato Grosso do Sul, with educators from a riverside schools. The writing of the text dialogues with photo pairs under the theoretical foundation of Ricardo Marín Viadel, Joaquin Roldán and Rafaèle Genet (2017), as a concept arising from a/r/tography, which places authors as creators, teachers and researchers in methodologies that are based in art.